Cystic Ovarian Disease in Rathi Cattle - Gupta, G N; Joshi, B K; bishnoi, B L; Gupta, A K; Joshi, R K; Vyas, S K; Gupta, K A; Pareek, P K; Sharma, S S (Annals of Arid Zone, 2016)
Cystic ovarian disease (COD) was studied in Rathi cows. The overall incidence of COD in rural and urban areas was 2.12 and 0.87%, respectively. Cysts were usually singie, smaller in size and located mostly on the right ovary (56.03%) with nymphomania as the predominant clinical sign. Biochemical estimations in serum revealed significantly higher values of chloride and significantly lower values of inorganic phosphorus (P<0.05) in cystic cows compared to normal cows. Enucleation was the principal treatment of COD (56.41%) in rural cows, whereas, GnRH (41.17%) was the major tre !mentÂ·in urban cows. A good number of untreated cows with COD (27.17%) also become pregnant without any treatment.